Soil moisture index in Pomurje: an example of Landsat 8 satellite data use - Davidovič, Danijel; Ivajnšič, Danijel (Journal for Geography, 2020)
This research demonstrates the methodological implementation of satellite imagery for evaluation of soil moisture in the case of Pomurje (Slovenia). The presented soil moisture index is a derivative of surface temperature and NDVI vegetation index, using spectral bands detected by optical and thermal sensor of the Landsat 8 satellite. The obtained values of the soil moisture index vary between 0 (low soil moisture) and 1 (high soil moisture). Furthermore, we observe the differences in soil moisture with regard to intensive or extensive agricultural land use. The calculated estimates of soil moisture in Pomurje reached values between 0.06–0.99, with statistically significant differences between higher values in forests and lower values in fields and other selected landuse categories. This approach to soil moisture assessment is useful for monitoring and planning agricultural and environmental activities at the landscape level and for evaluating the climate change impact on the humidity conditions in a given area.
Keywords: remote sensing; GIS; soil moisture index; Landsat; normalized difference vegetation index; land surface temperature